The current state of food safety in terms of 137Cs content compared to 2010 in the context of food safety - Kotelevych, V.; Pinsky, O. (Scientific Progress & Innovations, 2022)
The priority task of modern science and practice is to limit radionuclide intake into the human body. Among the measures of radiation protection for the population, the most difficult, but also the most important, is control over the content of radionuclides in food products, informing the people, and preventing the sale of food products that do not meet the permissible levels. Given the relevance of this issue, our research aimed to establish the current state of food safety concerning the content of 137Cs in the Polish region compared to 2010 in the context of food safety. According to the results of the analysis of publications, reporting documentation of the radiological department of the regional sanitary and epidemiological station of Zhytomyr and the State Production and Consumer Service for 2010, own research of samples of mushrooms, berries, the meat of domestic and wild animals, food products from private farms in the northern districts of Zhytomyr region, and reporting documentation of Zhytomyr and Rivne regions regional state laboratories of the State Service for Food Safety and Consumer Protection, state laboratories of veterinary and sanitary service at food markets of Zhytomyr and Zhytomyr region, Rivne and Rivne region (for 2010, 2017–2022) we found out that the content of radionuclides in mushrooms, berries, game and products of own production in areas of the Polissky region contaminated by the accident at the Chornobyl nuclear power plant in most cases significantly exceeds the permissible levels. This creates large doses of internal radiation and negatively affects the population's health. Exceeding DR-2006 in terms of 137Cs content is observed in samples from Novohrad-Volynskyi, Yemilchynskyi, Luhynskyi, Malynskyi, Narodytskyi, Ovrutskyi, Olevskyi districts. The most contaminated examples were from the Narodytskyi district, e. g. fresh mushrooms and berries – 2000 Bq/kg, dry – 3450 Bq/kg. The northern regions of the Rivne region have an extremely high content of 137Cs in food products, especially gifts of the forest. We determined the highest percentage of excesses in the examples of mushrooms and berries of forest origin in the Dubrovytskyi and Rakitnivskyi districts. The highest level of contamination of milk and meat was determined in 2010. In the first half of 2022, the DLVSE of food markets of the Zhytomyr region detected 3 examples with an excess of the radionuclide content of cesium-137 in 3 examples of dry mushrooms in Ovruch (2637.5 Bq/kg), fresh forest berries in Lugyny (1226.7 Bq/kg) and carrots (49 Bq/kg).